DAMPAK AI-BASED LEADERSHIP TERHADAP EFEKTIVITAS PEMBELAJARAN MELALUI PERAN MODERASI WORKPLACE SPIRITUALITY - St. Maizah; Munirul Abidin (re-JIEM (Research Journal of Islamic Education Management), 2025)
This study aims to analyze the effect of AI-Based Leadership on learning effectiveness moderated by Workplace Spirituality within Islamic educational institutions. The research background is grounded in the rapid advancement of artificial intelligence technology, which significantly transforms leadership patterns and instructional processes in modern educational settings. A quantitative approach with an explanatory research design was employed to examine causal relationships among the study variables. Primary data were collected through a closed questionnaire utilizing a five-point Likert scale, distributed to fifty-one educators at the Al-Hayatul Islamiyah Foundation in Malang, Indonesia, using purposive sampling technique. Data analysis was conducted using Moderated Regression Analysis (MRA) to test the proposed hypotheses. The findings reveal that AI-Based Leadership exerts a positive and statistically significant influence on learning effectiveness. Workplace Spirituality also demonstrates a direct positive effect and significantly moderates the relationship between AI-Based Leadership and learning effectiveness. These results underscore the strategic importance of integrating technology-driven leadership with spiritual values to foster an effective and meaningful learning environment. This study contributes to the development of integrative educational leadership models and recommends that educational institutions optimize artificial intelligence applications while preserving workplace spirituality to achieve sustainable and comprehensive improvements in learning quality for all stakeholders.